Multifaceted activity of cytokinin in leaf development shapes its size and structure in Arabidopsis - Skalák, Jan; Vercruyssen, Liesbeth; Claeys, Hannes; Hradilová, Jana; Černý, Martin; Novák, Ondřej; Plačková, Lenka; Saiz-Fernández, Iñigo; Skaláková, Patricie; Coppens, Frederik; Dhondt, Stijn; Koukalová, Šárka; et al. (Plant journal, 2019)
The phytohormone cytokinin has been shown to affect many aspects of plant development ranging from the regulation of the shoot apical meristem to leaf senescence. However, some studies have reported contradictory effects of cytokinin on leaf physiology. Therefore cytokinin treatments cause both chlorosis and increased greening and both lead to decrease or increase in cell size. To elucidate this multifaceted role of cytokinin in leaf development, we have employed a system of temporal controls over the cytokinin pool and investigated the consequences of modulated cytokinin levels in the third leaf of Arabidopsis. We show that, at the cell proliferation phase, cytokinin is needed to maintain cell proliferation by blocking the transition to cell expansion and the onset of photosynthesis. Transcriptome profiling revealed regulation by cytokinin of a gene suite previously shown to affect cell proliferation and expansion and thereby a molecular mechanism by which cytokinin modulates a molecular network underlying the cellular responses. During the cell expansion phase, cytokinin stimulates cell expansion and differentiation. Consequently, a cytokinin excess at the cell expansion phase results in an increased leaf and rosette size fueled by higher cell expansion rate, yielding higher shoot biomass. Proteome profiling revealed the stimulation of primary metabolism by cytokinin, in line with an increased sugar content that is expected to increase turgor pressure, representing the driving force of cell expansion. Therefore, the developmental timing of cytokinin content fluctuations, together with a tight control of primary metabolism, is a key factor mediating transitions from cell proliferation to cell expansion in leaves.
Keywords: genová ontologie; proliferace buněk; Gene Ontology; proteom; listy rostlin; Proteome; zvětšování buněk; Plant Leaves; signální transdukce; cytokininy; Signal Transduction; Cytokinins; Cell Enlargement; Cell Proliferation; Arabidopsis; transkriptom; regulátory růstu rostlin; Transcriptome; Plant Growth Regulators